Early and late new‐onset of atrial fibrillation in acute coronary syndromes: Their differences in mortality and cardiac event. Issue 3 (4th March 2022) - Santos, Helder; Santos, Mariana; Almeida, Inês; Paula, Sofia B.; Almeida, Samuel; Chin, Joana; Almeida, Lurdes; ,
Abstract: Background: In a stressful situation like acute coronary syndrome (ACS), the occurrence of the first episode of atrial fibrillation is more frequent. The impact of the timing occurrence of AF new‐onset (nAF) in the setting of ACS is still debatable. Methods: Multicenter retrospective study based on the Acute Coronary Syndrome Portuguese National Registry, including 29 851 patients admitted for ACS between 1/10/2010 and 4/09/2019. The group with early nAF ‐ nAF in the first 48 h of hospitalization; and late nAF ‐ patients with nAF after the first 48 h of in‐hospital admission. Results: New‐onset AF was identified in 1067 patients, nonetheless, just 38.1% had late nAF. The group with late nAF presented more cardiovascular comorbidities and worse left ventricular ejection fraction. Late nAF patients received more anti‐arrhythmic therapy, and early nAF had a higher beta‐block prescription. Early nAF had higher rates of in‐hospital complications, on the other hand, late nAF group exhibited more mortality and readmission at one year follow‐up. Multiple logistic regression revealed that symptoms onset to the first medical contact time, admission hemoglobin <12 g/dl, right bundle branch block at admission, and diuretic therapy during the hospitalization for ACS were predictors of late nAF in ACS. Conclusions: The ACS population could be divided by the timing of nAF occurrence into the two groups with different characteristics, therapeutic approaches, and outcomes. Late nAF patients had a worse prognosis at 1 year follow‐up, however, the early nAF group had more major adverse cardiac events during the hospitalization for ACS. Abstract : The presence of comorbidities favors the occurrence of late new onset atrail fibrillation in the setting of acute coronary syndrome, and that these patients had the worst prognosis.